Additional file 2 of Patterns of self-medication and intention to seek pharmacist guidance among older adults during the COVID-19 pandemic in Macao: a cross-sectional study - Zheng, Yu; Tang, Pou Kuan; Hu, Hao; Ung, Carolina Oi Lam (figshare, 2024)
Supplementary Material 2